Universal learning machine with genetic programming - Re, Alessandro (2019)
Re, A., Vanneschi, L., & Castelli, M. (2019). Universal learning machine with genetic programming. In J. J. Merelo, J. Garibaldi, A. Linares-Barranco, K. Madani, K. Warwick, & K. Warwick (Eds.), Proceedings of the 11th International Joint Conference on Computational Intelligence (Vol. 1, pp. 115-122). (IJCCI 2019 - Proceedings of the 11th International Joint Conference on Computational Intelligence). Viena: SciTePress.